P‐21: The Effect of Thermal Annealing Sequence on the Performance of Self‐Aligned Top‐Gate a‐IGZO TFTs. Issue 1 (May 2017) - Lu, Hongjuan; Zhang, Letao; Zhou, Xiaoliang; Zhang, Xiaodong; Liang, Ting; Zhang, Shengdong
Abstract : The effects of thermal annealing sequence on the performance of self‐aligned top‐gate amorphous InGaZnO (a‐IGZO) thin‐film transistors (TFTs) are investigated. The TFTs annealed before the formation of gate electrode exhibit good electrical performance, however, the TFTs annealed after the formation of gate electrode show abnormal electrical performance. It is shown that the performance of self‐aligned top‐gate a‐IGZO TFTs is very sensitive to the annealing sequence. As a result, an optimized annealing process is presented and demonstrated.